PENGEMBANGAN SISTEM INFORMASI INVENTARIS ALAT BERAT BEKAS UNTUK MENINGKATKAN AKSESIBILITAS DENGAN METODE DESIGN THINKING - Junaedi, Junaedi; Mudjahidin, Mudjahidin (Smart Education, 2026)
Abstract: The mining sector in Indonesia continues to grow, leading to an increased utilization of heavy equipment in operational activities. PT X, as a mining contractor, faces significant challenges in managing used heavy equipment inventory, which consists of hundreds of units that still possess potential economic value. The main issues include limited data accessibility, outdated information, low data accuracy and transparency, complex data structures across multiple Excel files, and manual administrative processes for disposed documents. These conditions potentially reduce inventory management efficiency and increase the risk of inaccurate decision making. This study aims to develop a web-based prototype of a used heavy equipment inventory information system to improve data accessibility, accuracy, transparency, and real-time data update efficiency. The research utilizes inventory data from PT X covering the period from 2010 to 2024. The design thinking method is applied through the stages of empathize, define, ideate, prototype, and test. The empathize stage involves interviews, observations, SCOPES analysis, and activity system mapping, followed by the define stage using affinity diagrams, point of view, and how might we. The ideate stage employs SCAMPER and a priority matrix to identify key solution features, which are then implemented in a high-fidelity prototype. Prototype usability is evaluated using the System Usability Scale (SUS). The results show a SUS score of 74.29, indicating good usability and acceptability. The proposed system is expected to support faster, more accurate, and more transparent strategic decision-making in used heavy equipment inventory management. Keyword: information system, inventory used heavy equipment, improving accessibility, design thinking, asset management. Abstrak: Sektor pertambangan di Indonesia terus berkembang sehingga berdampak pada meningkatnya penggunaan alat berat dalam operasional perusahaan. PT X sebagai kontraktor pertambangan menghadapi permasalahan dalam manajemen inventaris alat berat bekas yang berjumlah ratusan unit dan masih memiliki nilai ekonomis. Permasalahan utama meliputi keterbatasan aksesibilitas data, data yang tidak selalu diperbarui, rendahnya akurasi dan transparansi, kompleksitas struktur data pada berbagai file Excel, serta proses administrasi dokumen disposed yang masih dilakukan secara manual. Kondisi ini berpotensi menurunkan efisiensi pengelolaan inventaris dan meningkatkan risiko pengambilan keputusan yang kurang akurat. Penelitian ini bertujuan mengembangkan prototipe sistem informasi inventaris alat berat bekas berbasis web untuk meningkatkan aksesibilitas, akurasi, transparansi, serta efisiensi pembaruan data secara real-time. Data penelitian berasal dari inventaris alat berat PT X periode 2010–2024. Metode design thinking digunakan melalui tahapan empathize, define, ideate, prototype, dan test. Tahap empathize dilakukan melalui wawancara, observasi, analisis SCOPES, dan activity system mapping, dilanjutkan define menggunakan affinity diagram, point of view, dan how might we. Pada tahap ideate digunakan SCAMPER dan matriks prioritas, kemudian dikembangkan high-fidelity prototype dan diuji menggunakan System Usability Scale (SUS). Hasil pengujian menunjukkan skor SUS sebesar 74,29 yang tergolong good usability dan acceptable. Prototipe yang dihasilkan diharapkan mendukung pengambilan keputusan yang lebih cepat, akurat, dan transparan Kata kunci: sistem informasi, inventaris alat berat bekas, meningkatkan aksesibilitas, design thinking, manajemen aset